The Role of Self-esteem and Optimism in Job Satisfaction among Teachers of Private Universities in Bangladesh - Ahmed, Mozumdar Arifa (Asian Business Review, 2012)
The objective of this study was to investigate the role of self- esteem and optimism in job satisfaction among teachers of private universities in Bangladesh. The measuring instruments used in this study were: 1. Self-Esteem Scale (SES) (Rosenberg’s, 1965) for measuring self-esteem. 2. Life Orientation Test (LOT) (Scheier& Carver, 1985) for measuring Optimism. 3. Job Satisfaction Survey (JSS) (Spector, 1985) for measuring job satisfaction. According to the objective of the present study the obtain data were analysed using Pearson product moment correlation. The survey results revealed that self-esteem and optimism is significantly positively correlated with teacher’s job satisfaction.
Keywords: Teaching; Teachers; Self-esteem; Optimism; Motivation; Job Satisfaction